Chlorine partitioning near the polar vortex boundary observed with ground-based FTIR and satellites at Syowa Station, Antarctica in 2007 and 2011 - Nakajima, Hideaki; Murata, Isao; Nagahama, Yoshihiro; Akiyoshi, Hideharu; Saeki, Kosuke; Kinase, Takeshi; Takeda, Masanori; Tomikawa, Yoshihiro; Jones, Nicholas B. (2019)
We retrieved lower stratospheric vertical profiles of O 3 , HNO 3 , and HCl from solar spectra taken with a ground-based Fourier-Transform infrared spectrometer (FTIR) installed at Syowa Station, Antarctica (69.0° S, 39.6° E) from March to December 2007 and September to November 2011. This was the first continuous measurements of chlorine species throughout the ozone hole period from the ground in Antarctica. We analyzed temporal variation of these species combined with ClO, HCl, and HNO 3 data taken with the Aura/MLS (Microwave Limb Sounder) satellite sensor, and ClONO 2 data taken with the Envisat/MIPAS (The Michelson Interferometer for Passive Atmospheric Sounding) satellite sensor at 18 and 22 km over Syowa Station. HCl and ClONO 2 decrease occurred at both 18 and 22 km, and soon ClONO 2 was almost depleted in early winter. When the sun returned to Antarctica in spring, enhancement of ClO and gradual O 3 destruction were observed. During the ClO enhanced period, negative correlation between ClO and ClONO 2 was observed in the time-series of the data at Syowa Station. This negative correlation was associated with the distance between Syowa Station and the inner edge of the polar vortex. We used MIROC3.2 Chemistry-Climate Model (CCM) results to see the comprehensive behavior of chlorine and related species inside the polar vortex and the edge region in more detail. From CCM model results, rapid conversion of chlorine reservoir species (HCl and ClONO 2 ) into Cl 2 , gradual conversion of Cl 2 into Cl 2 O 2 , increase of ClO when sunlight became available, and conversion of ClO into HCl, was successfully reproduced. HCl decrease in the winter polar vortex core continued to occur due to the transport of ClONO 2 from the subpolar region to higher latitudes, providing a flux of ClONO 2 from more sunlit latitudes into the polar vortex. Temporal variation of chlorine species over Syowa Station was affected by both heterogeneous chemistry related to Polar Stratospheric Cloud (PSC) occurrence deep inside the polar vortex, and transport of an NO x -rich airmass from lower latitudinal polar vortex boundary region which can produce additional ClONO 2 by reaction of ClO with NO 2 . The deactivation pathways from active chlorine into reservoir species (HCl and/or ClONO 2 ) were found to be highly dependent on the availability of ambient O 3 . At an altitude where most ozone was depleted in Antarctica (18 km), most ClO was converted to HCl. However, at an altitude where there were some O 3 available (22 km), additional increase of ClONO 2 from initial value can occur, similar to the case in the Arctic.